Development of a Moving Bed Reactor for Thermochemical Heat Storage Based on Granulated Ca(OH)2 - Cosquillo Mejia, Aldo; Afflerbach, Sandra; Linder, Marc; Schmidt, Matthias (Processes, 2022)
Calcium hydroxide is promising for thermal energy storage due to its low cost and high energy density. Nevertheless, the powdered material is cohesive and has low thermal conductivity which is a major challenge for the operation of moving bed reactors. One approach to facilitate the movement of the reaction bed is the stabilisation of the particles through the coating of Ca(OH)2 granules with Al2O3 particles. In this work, a newly designed reactor concept was specifically developed for testing coated Ca(OH)2 granules. The design allows for the movement of the reaction bed by gravity assistance and direct heating of the particles by a counter current gas flow. The operation was successfully demonstrated and proved to achieve high heat transfer between gas and granules. Furthermore, the movement of the reaction bed was achieved after the discharging phase. Two batches of uncoated and coated Ca(OH)2 granules were subject of 10 thermochemical cycles in this reactor. The cycling stability, structural integrity, mechanical stability, morphology and phase composition of the granules were analysed. Full conversion of both samples was demonstrated for the entire experimental series. It was found that the alumina coating enhances the mechanical stability of the granules under reaction conditions.